Hyperspectral Image Denoising with a Spatial– Spectral View Fusion Strategy (International Journal of Engineering and Computer Science, 2015)
The paper discusses about the hyper spectral and MS-PAN fusion system, the first part discusses the introduction to fusion imaging and its types, and second part deals with work done by authors with respect to the fusion imaging, third section discusses the proposed system of MS-PAN image fusion with RDWT with reduced noise error and statistical comparison of results.